Introduction to the Festschrift for Prof. D.F. (Francois) Tolmie - L. Sutton; N.E. Müller van Velden (Acta Theologica)
The articles in this Supplementum are dedicated to our colleague Professor Francois Tolmie to mark the occasion of his retirement in 2024. In the Faculty of Theology and Religion at the University of the Free State, Prof. Tolmie is regarded as the historical memory of the Faculty as he dedicated his life to this institution – both as a student and as a professor. In later years of his career, he also led the Faculty as Dean. He is notorious for being an excellent editor, focusing on detail and precision. Internationally, he is acclaimed as both a Johannine scholar and a Pauline scholar, a feat few scholars can claim. Those who know him will testify that he treats people with the utmost respect, and that it is hard to find a humbler person.